ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PT KAPUAS PELUMASINDO LESTARI PONTIANAK - B51112069, Andre Purwadi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Inventory is crucial in a trading company, since inventory is the greatest asset value compared to other current assets in the balance sheet of the company. In the case of the purchase of inventory, companies usually make purchases in bulk. Thus the necessary internal controls in recording procedures, assessment and determination of the cost of inventory in the company to maintainÂ  the smooth operation of the company. Inventory a company will experience a change. To determine the changes required recording and assessment of each transaction. The aim of this study was to determine whether the system of internal control over merchandise inventory inflows and outflow of goods PT. Kapuas Pelumasindo Lestari adequate. Internal control system at PT. Kapuas Pelumasindo Lestari not effective, because there are weaknesses that lead to negligence and fraud occur therein. Principle of supplying too much meddling company in the purchase of goods to the supplier. There is still work concurrently. Upon receipt of merchandise from the expedition, the goods are not counted and checked thoroughly regrading quality and quantity. Keywords : Internal Control System, Merchandise Inventory.